Synthesis of 6,7-Dibromoflavone and Its Regioselective Diversification via Suzuki–Miyaura Reactions - Jordán, Sándor; Pajtás, Dávid; Patonay, Tamás; Langer, Peter; Kónya, Krisztina (Synthesis, 2017)
The first synthesis pathway to 6,7-dibromoflavone and its transformations to 7-aryl-6-bromo- and 6,7-diarylflavones by Suzuki–Miyaura reactions are presented. Due to the different electronic effects of bromo substituents, the first attack proceeded with good site selectivity at position 7.
Keywords: palladium; Suzuki–Miyaura reaction; flavones; catalysis; regioselectivity